Heart failure hospitalization trends during a very long-term follow-up up to 18 years. (25th November 2020) - Zamora, E; De Antonio, M; Domingo, M; Santiago-Vacas, E; Codina, P; Santesmases, J; Troya, M.I; Diez-Quevedo, C; Boldo, M; Alonso, N; Gonzalez, B; Rivas, C; et al.
Abstract: Background: Heart Failure (HF) is the first cause of hospitalizations in people older than 65 years. Often patients suffer recurrent hospital admissions. Objective: To assess recurrent HF-related hospitalizations during very long-term follow-up in a cohort of HF outpatients managed in an ambulatory structured HF Unit. Methods: End of follow-up was 31.8.2019 (at least 1-year follow-up for alive patients, up to 18 years). Heart failure hospitalizations were defined as unplanned hospitalizations of at least 24 hours due to worsening heart failure and were identified from clinic records, hospital wards, or electronic Catalan history record. Death was recorded from the same sources and Spanish Health System and Spanish Death Registry. Lost information during follow-up was adequately censored (1 patient for survival status and 37 for HF-related hospitalizations). Results: A total of 2355 patients were included. Follow-up span a total of 12, 472 patients-years. 1682 HF-related hospitalizations were recorded in 725 patients (13.5 per 100 patients-years). Number of admissions ranged from 0 in 1630 patients to 22 in 1 patient (patients with hospitalizations, median 2 [Q1-Q3, 1–3]; 118 patients had 4 or more hospitalizations). HF hospitalization density incidence was higher during the 10 first years in patients with HF hospitalizations in the precedent year before HF Clinic baseline visit (table). By contrast, if only patients who died during follow-up were considered (N=1299), hospitalization trends significantly increased in their last period of life: 11.7%, 8.9%, 13.6%, 20.8% and 44.9% from the first to the last period (quintile) of their trajectory, respectively. Conclusions: HF hospitalizations occur during the whole HF trajectory, with an increasing trend at the end of the every patient trajectory. Funding Acknowledgement: Type of funding source: None